Reactions of platinum complexes with 4, 7-phenanthroline: crystal structures of mono- and binuclear platinum(II) complexes containing 4, 7-phenanthroline. Issue 18 (16th September 2016) - Momeni, Badri Z.; Fathi, Nastaran; Shafiei, Maliheh; Ghasemi, Fahimeh; Rominger, Frank
Abstract: The reaction of a mixture of cis and trans -[PtCl2 (SMe2 )2 ] with 4, 7-phen (4, 7-phen = 4, 7-phenanthroline) in a molar ratio of 1 : 1 or 2 : 1 resulted in the formation of mono and binuclear complexes tran s-[PtCl2 (SMe2 )(4, 7-phen)] (1 ) and trans -[Pt2 Cl4 (SMe2 )2 (μ-4, 7-phen)] (2 ), respectively. The products have been fully characterized by elemental analysis, 1 H, 13 C 1 H, HHCOSY, HSQC, HMBC, and DEPT-135 NMR spectroscopy. The crystal structure of1 reveals that platinum has a slightly distorted square planar geometry. Both chlorides are trans with a deviation from linearity 177.66(3)°, while the N–Pt–S angle is 175.53(6)°. Similarly, the reaction of a mixture of cis and trans -[PtBr2 (SMe2 )2 ] with 4, 7-phen in a 1 : 1 or 2 : 1 mole ratio afforded the mono or binuclear complexes trans -[PtBr2 (SMe2 )(4, 7-phen)] (3 ) and trans -[Pt2 Br4 (SMe2 )2 (μ-4, 7-phen)] (4 ), respectively. The crystal structure of trans -[Pt2 Br4 (SMe2 )2 (μ-4, 7-phen)].C6 H6 reveals that 4, 7-phen bridges between two platinum centers in a slightly distorted square planar arrangement of the platinum. In this structure, both bromides are trans, while the PtBr2 (SMe2 ) moieties are syn to each other. NMR data of mono and binuclear complexes of platinum1 –4 show that the binuclear complexes exist in solution as a minor product, while the mononuclear complexes are major products. Abstract :